ENTEREPRENEURSHIP EDUCATION: STUDY EXPERIENCE AND PROSPECTS IN UKRAINE - Melnychenko, Olga (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to the development of entrepreneurship education in the context of the educational process in universities. It examines the relationship of the business sector and university education in modern changes. The author argues that the system of education at the university level is not currently able to develop the students’ motivation and skills that promote innovation and entrepreneurship. Particular attention is paid to the subject matter «Pedagogy of enterprise» as an essential part of entrepreneurship education. The article stated the fact that the entrepreneurship education requires special education teaching methods, teaching process, teachers and staff who currently do not have universities. This requires certain changes in the didactic part of the learning process: the concept of learning, training and work programs, teaching methods, focus on practical learning and more. Increasing the request of the society on entrepreneurship training and the development of entrepreneurship has become an important task before the modern academic community. Entrepreneurship is a condition that includes the personal abilities, skills and motivation that lead people to engage in creative activities to create new products and services, develop business according to market requirements. In addition to personal values, business has a clearly defined social potential because it has to take into account the needs and requirements of potential customers, thereby improving the conditions of their existence. In addition, the business requires the creation of new jobs, a new team and management. For these reasons, entrepreneurship training and entrepreneurial initiative is seen as a key factor in the development of modern societies. The development of business initiatives and entrepreneurship in Western European countries (especially in EU countries) is associated with a number of factors: the rapid aging of the population in most countries, reduction of the workforce in most countries, increased competition from new countries offering cheaper labor. The level of business education in the EU lags behind the development of business education US and Canada.Today in Europe there is a relatively low level of entrepreneurship, which is reflected in the lack of business education in the educational policy of the European countries and promoting entrepreneurial skills to create new opportunities in the community. The development of entrepreneurship and initiative can contribute to social cohesion of society by increasing employment, economic benefits and income and job satisfaction. However, both the national (political level) and in education the problem is rarely seen as a strategic component of national policy. Although the problem of business education may be quite relevant in universities, because they have scientific, technological and innovation potential.In this case, the learning process requires changes in the content, methodologies and training tools, due to interdisciplinary orientation and practical business education. The purpose of the article: define and explain the pedagogical point of view of the concept of entrepreneurship education such as how teaching methods to develop the entrepreneurial spirit, initiative, critical thinking and provide practical skills for starting your own business and create a new company. Task: To justify the possibility of practical training in the study course «Pedagogy of entrepreneurship» actions that can be played both in the classroom and beyond; prove practical experience of entrepreneurship can be presented in a variety of forms and methods for the various stages of training. As Ukrainian educational environment has experience in teaching such subjects as «Pedagogy of entrepreneurship» because among educators’ term «education entrepreneurship» and «entrepreneurship» are often perceived as related identical terms, but for many people in education and the business community mean the same exactly. Therefore, determining the specific «Entrepreneurship Pedagogy», its concept, complex modern teaching methods will make the learning process on the one hand, greater awareness and responsibility of students, on the other hand, focus on the practical implications of teacher training. Today almost all schools, university colleges and universities in Europe in prepare of business education and business development initiatives. Conclusion: «Pedagogy of entrepreneurship» performs important tasks that put society today, solves the problem of entrepreneurship and enterprise, provides practical skills in business management and create their own campaigns. In the long term this will promote and dissemination of business education in Ukraine as in secondary and high schools, and will develop entrepreneurial thinking in the early stages of training.